Gender in Urban Transport in Nairobi, Kenya : Volume 1. Mobility - Kishiue, Akiko (World Bank, Washington, DC, 2020)
Transport is traditionally a male-dominated sector. The realization that the sector and its subsystems have been conceived, designed, and matured from either a male-oriented or a gender-neutral perspective is thus unsurprising. In Kenya, discussion about gender and related aspects has been on the rise since the formulation of the Integrated National Transport Sector Policy (2009), which acknowledged that gender inequality exists in access and mobility, particularly in informal urban settlements in Kenya. There is ample potential for the transport sector to generate significant changes in women’s productivity and empowerment, while ensuring equitable access to opportunities is offered for both men and women. This is what Kenya’s Vision 2030, the country’s blueprint for development, advocates for and is committed to enact. This study encompasses two independent analyses on mobility and employment in urban transport for the Kenyan capital context. Its findings are presented in two volumes. Volume 1 presents Mobility and Volume presents Employment.